Utilization of Corn and Ginger for Intensive Maintenance of Kampung Chicken In Gemah Ripah Farmer Group at Kucur, Dau, Malang - Achmanu Achmanu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
AbstractThe aims of the activity was to increase knowledge and skills on intensive kampung chicken management for the community, especially the members of farmer group of GemahRipahat Kucur Village, DistrictDau, Malang, East Jawa. The method used was the transfer of knowledge and skills through training and demonstration for the community as participant. The results of demonstration plots showed that the cultivation of kampungchicken by intensive system with formulated feed could reduce the cost of feed, and the addition of ginger in chicken feed improved the health of chicken, increased body weight gain, and reduced abdominal fat. Evaluation activities showed that the participants were responding positively to the lecture material, training and demonstration. It is suggestedthat the extension activities should be carried out more about the marketing of effective and profitablechicken farm production, and hatchery management counseling. Keywords: chicken farming, corn, feed, farmer group, ginger, kampung chicken